Job Autonomy on Innovative Behaviour with Work Engagement as a Mediating Variable - Claudya Rahmasari Jhody; Yuki Fitria (Human Resource Management Studies, 2022)
The purpose of this study was to examine: (1) The effect of job autonomy on innovative behaviour in Whiz Prime Hotel Padang employees. (2) The effect of job autonomy on work engagement of Whiz Prime Hotel Padang employees. (3) The effect of work engagement on innovative behaviour of Whiz Prime Hotel Padang employees. (4) The effect of job autonomy on the innovative behaviour of Whiz Prime Hotel Padang employees through work engagement. The population in this study were all employees at Whiz Prime Hotel Padang totaling 61 people. While the number of samples in this study was determined by using the total sampling method, namely making the entire population in the study a sample, so that the number of samples obtained was 61 people. The analytical technique used is SEM analysis using smart PLS3. The results of this study indicate that: (1) job autonomy has a positive and significant effect on innovative behaviour in Whiz Prime Hotel Padang employees. (2) Job autonomy has a positive and significant effect on work engagement for Whiz Prime Hotel Padang employees. (3) Work engagement has a positive and significant effect on the innovative behaviour of Whiz Prime Hotel Padang employees. (4) Job autonomy has a significant effect on the innovative behaviour of Whiz Prime Hotel Padang employees with work engagement as a mediating variable